Isolation and Genomic Characterization of a Novel Porcine Reproductive and Respiratory Syndrome Virus 1 from Severely Diseased Piglets in China in 2024 - Shuai Yang; Meng Cui; Chen Li; Ming Qiu; Xiaoyang Zhu; Yanhan Lin; Yifan Meng; Yuejia Qiu; Wenhao Qi; Hong Lin; Wanglong Zheng; Jianzhong Zhu; et al. (Veterinary Sciences)
Since the first isolation of the porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) BJEU06-1 strain from a Beijing pig farm in 2006, more and more PRRSV-1 isolates have been identified in China. In this study, we performed the routine detection of PRRSV-1 using 1521 clinical samples collected in 12 provinces/cities from February 2022 to May 2024. Only three lung samples from severely diseased piglets collected in January 2024 were detected as PRRSV-1-positive (0.197%, 3/1521). A PRRSV-1 strain (AHEU2024-2671) was successfully isolated in primary alveolar macrophages (PAMs) but not in Marc-145 cells. Genome sequencing showed that the AHEU2024-2671 isolate shared the highest genome similarity (90.67%) with the SC2020-1 isolate but only 84.01% similarity with the predominant BJEU06-1 strain. Noticeably, the AHEU2024-2671-like isolates not only contained deletions in nsp2 and the GP3-GP4 overlap region, but also contained a unique 6 nt deletion between nsp12 and the ORF2 gene. Furthermore, a genome-based phylogenetic tree supported that the AHEU2024-2671-like isolates form a novel subgroup within subtype 1. Overall, this study not only supported the idea that PRRSV-1 is rapidly evolving in Chinese swine herds, but also pulled the alarm that novel PRRSV-1 isolates with potentially increased pathogenicity might already exist in China, although they are still rarely detected among Chinese pigs.